Design Innovation of Ethnic Cultural Wisdom Tourism Products Based on Digital Information Technology. (25th August 2022) - Zhou, Yi; Chen, Shaohan
Abstract : With the improvement of people's living standards, ethnic tourism has begun to develop in an all-round way, and correspondingly, ethnic cultural products have become more and more dazzling. However, the current tourists' satisfaction with ethnic cultural tourism products is generally low, so the innovative design of tourism products is an important means to improve the satisfaction of tourism products. The purpose of this paper was to use digital information technology to study the innovation of national cultural wisdom tourism product design and to optimize tourism products. This paper first expounded the experiential design of ethnic cultural tourism products which applies the TEAR theory, and the ASEB grid analysis introduced the four factors of theme, environment, activity, and reaction, analyzed the experience of tourism from the perspective of tourists, then introduced the extraction and development process of digital information technology, and then built a three-dimensional digital model of ethnic cultural tourism product design to lay a solid foundation for product design. In addition, this paper took the development of ethnic cultural tourism products in Yunnan ethnic villages as a case to investigate and analyze the tourist market and tourist needs and finally put forward some product design ideas and suggestions. Through the research and analysis of tourists, it is found that there are more young and middle-aged tourists in Yunnan ethnic villages, and most of them travel with their families. According to the survey of tourists' preferences, more than 80% of tourists like high-quality and low-cost tourism products, and nearly 50% of tourists want to gain a thinking experience in tourist attractions. The most popular forms of tourists were ethnic art and traditional culture. Therefore, designers can design tourism products according to the preferences of tourists and improve the satisfaction of tourism products.